2020
DOI: 10.17485/ijst/v13i30.1150
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity evaluation of CELNORM, a nutritional health supplement, on MCF7 breast cancer cells

Abstract: Objective: To evaluate the in vitro cytotoxic potential of CELNORM, a nutritional health supplement, on MCF7 human adenocarcinoma breast cancer cells. Methods: Briefly, MCF7 cells were cultured for 24 hours in complete growth medium containing fetal bovine serum and antibiotics and exposed to various concentrations (500, 250, 125, 62.5, 31.25, 15.625, 7.8125, 3.906 micrograms/mL) of CELNORM for a period of 24 hours. Cell viability/death was assessed qualitatively by microscopy and quantitatively by MTT assay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Curcumin, when combined with other natural substances, significantly increased clonogenic inhibition and induced cell apoptosis. One previous study that showed the efficacy of CELNORM on breast cancer has detailed its action against halting the proliferation of breast cancer cells when tested in MCF7 cell lines (Sathya et al, 2020). In terms of morphological features and cell proliferation inhibition, this combination of therapies generated a consistent response in both colon and lung cancer cell lines.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Curcumin, when combined with other natural substances, significantly increased clonogenic inhibition and induced cell apoptosis. One previous study that showed the efficacy of CELNORM on breast cancer has detailed its action against halting the proliferation of breast cancer cells when tested in MCF7 cell lines (Sathya et al, 2020). In terms of morphological features and cell proliferation inhibition, this combination of therapies generated a consistent response in both colon and lung cancer cell lines.…”
Section: Discussionmentioning
confidence: 89%
“…At first, stock of CELNORM and its constituent have been made at a concentration of 1mg/ml in DMEM containing 300 µl of DMSO. Then two groups (A and B) of extract supplemented with DMEM were prepared at different concentrations individually with all four extracts and CELNORM according to the previously published work (Sathya et al, 2020). Two cell lines (HCT116 and A549 cells) were used separately to study the effect of CELNORM and its components in the two treatment groups individually.…”
Section: Preparation Of Celnorm and Treatment With Celnorm And Its Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…Treating A549 cells with cucurbitacins for ~21 days showed positive results for inhibiting metastasis by regulating the levels of cyclooxygenase 2, matrix metalloproteinase 9, and cyclin D11 [64]. Similarly, other cucurbitacins were observed to inhibit angiogenesis in MDA-MB-231 and MCF-7 cancer cells by inhibiting the JAK/STAT pathways [65].…”
Section: Antiangiogenic and Antimetastatic Mechanismsmentioning
confidence: 94%